Encapsulation of functional oils by spray drying and their stability in spray-dried powder - Asmaliza Abd Ghani; Ehime University . The United Graduate School of Agricultural Sciences (2017)
Asmaliza Binti Abd Ghani (2017). Encapsulation 0f Functional Oils hy pray Drying and their Stability in Spray-Dried Powder. PhD Dissertation, Ehime University, Japan, p 123.
Keywords: spray drying, encapsulation, squalene, fish oil, oil-droplet diameter, sodium caseinate, transglutaminase, stability, CLSM, fluorenscence intensity, surface oil content, dextrose equivalent, encapsulation yield, peroxide value, dextro e equivalent The spray drying process is commonly technique for encapsulation of functional food ingredients such as flavorings, colorings, sweeteners and oils. The benefits of thi technique include the controlled release of encapsulated ingredients, which affects the nutritional content. The objective of this dissertation was to investigate the effect of oil-droplet diameter, wall materials such as maltodextrin (MD) with variou dextrose equivalents (DE) and ernul ifier on the tability of functional oil in spray-dried powder.
The stability of squalene oil (SO) retention in spray-dried powder were investigated. SO droplet diameter significantly affected the oxidation stability of the oil in pray-dried powders. The degradation behavior of SO powders at 105°C was correlated using the Avrami equation. This oxidation mechanism of SO in pray-dried powder might be estimated the propagative transfer of radical oxidation between oil-droplet particle. SQ ernul ified with 5 wt% PNC and mall oil droplet had better oxidative stability when compared with 5 wt% NC.
The stability of SO in the pray-dried powder was also investigated at three different temperatures, 50, 70, and 105°C. Spray-dried powder of emulsified SO were formed with 3, 5 and 8 wt% of NC to total olid powder and at three homogenization pressures. The reconstituted oil-droplet diameters were obtained about 0.69-0.77 ps", 0.47-0.61 J.tm and 0.19-0.27 J.tm at 20, 50 and 100 MPa highpressure homogenization, respectively. SO at 100 MPa was more table at high temperature 105°C and SO at 20 MPa had lower degradation rate at 50 and 70 ° . The frequency factor of degradation rate constant was also correlated to the activation energy as the chemical compensation relationship. These results suggest that oil-droplet diameter might be a major controlling factor of the degradation of SO in spray-dried powder.
The surface oil ratio of encapsulated fish oil powders was measured with two types of oil-droplets diameter, nano and micro using the hexane washing method. A matrix composed of MD and NC was used as the wall material to encapsulate the fi h oil, and Nile red wa used to stain the oil. Fluorescence intensity using confocal laser scanning microscopy (CLSM) indicates good correlation between the oil content and fluorescence intensity.
A 'mali::a Binti Abd Ghani (2017). Encap .ulation 0/ Functional Oils hy pray Drying and their Stability in Spray-Dried Powder. PhD Dissertation, Ehime University, Japan, p 123.
Keywords: spray drying, encapsulation, squalene, fish oil, oil-droplet diameter, sodium caseinate, transglutaminase, stability, CLSM, fluorenscence intensity, surface oil content, dextrose equivalent, encapsulation yield, peroxide value, dextro e equivalent
The spray drying process is commonly technique for encapsulation of functional food ingredients such as flavorings, colorings, sweeteners and oils. The benefits of thi technique include the controlled release of encapsulated ingredients, which affects the nutritional content. The objective of this dissertation was to investigate the effect of oil-droplet diameter, wall materials such as maltodextrin (MD) with variou dextrose equivalents (DE) and ernul ifier on the tability of functional oil in spray-dried powder.
The stability of squalene oil (SO) retention in spray-dried powder were investigated. SO droplet diameter significantly affected the oxidation stability of the oil in pray-dried powders. The degradation behavior of SO powders at 105°C was correlated using the Avrami equation. This oxidation mechanism of SO in pray-dried powder might be estimated the propagative transfer of radical oxidation between oil-droplet particle. SQ ernul ified with 5 wt% PNC and mall oil droplet had better oxidative stability when compared with 5 wt% NC.
The stability of SO in the pray-dried powder was also investigated at three different temperatures, 50, 70, and 105°C. Spray-dried powder of emulsified SO were formed with 3, 5 and 8 wt% of NC to total olid powder and at three homogenization pressures. The reconstituted oil-droplet diameters were obtained about 0.69-0.77 ps", 0.47-0.61 J.tm and 0.19-0.27 J.tm at 20, 50 and 100 MPa highpressure homogenization, respectively. SO at 100 MPa was more table at high temperature 105°C and SO at 20 MPa had lower degradation rate at 50 and 70 ° . The frequency factor of degradation rate constant was also correlated to the activation energy as the chemical compensation relationship. These results suggest that oil-droplet diameter might be a major controlling factor of the degradation of SO in spray-dried powder.
The surface oil ratio of encapsulated fish oil powders was measured with two types of oil-droplets diameter, nano and micro using the hexane washing method. A matrix composed of MD and NC was used as the wall material to encapsulate the fi h oil, and Nile red wa used to stain the oil. Fluorescence intensity using confocal laser scanning microscopy (CLSM) indicates good correlation between the oil content and fluorescence intensity. The neap ulati n efficiency is affected by ev ral parameter uch a oil-droplet diameter, olid and oil contents, and proce ing conditions in pray drying. ffect of DE valu of MD on th stability of fish oil in spray-dried powder was investigated. NC (3 wt%), MD (DE = 8, 11, 19, 25, and 40) as wall material, and fish oil as core material were used to form spray-dried powders with 30, 40, 50 and 60 wt% of oil load to total solid content. Feed emulsions were prepared using a rotor-stator homogenizer and/or a high-pressure homogenizer at 20 or 100 MPa. The percentage of microcapsules with a vacuole was 73, 39, and 38%. Peroxide values (PVs) were measured for incubated the microcapsule at 60°C. The microcapsule prepared with MD of DE = 25 and 19 had lower PVs than those prepared with MD of DE = 11. The surface-oil ratio was remarkably increased when the ratio, E = (d/dp) of the average reconstituted oil-droplet diameter (de) to the average particle diameter (dp) was higher than 0.01. The oil-droplet diameter might affect the stability offi h oil in pray-dried p wder
The composition of material in feed emulsion i important for the oil encapsulation efficiency. The emulsification method is important to control the oil-droplet diameter of fish oil powder. The oildroplet diameter affected significantly surface-oil ratio and stability of functional oil in spray-dried powder.
Thesis (Degree of Doctor of Philosophy in Applied Bioresource Science) - Ehime University
Includes bibliographical references (pages 103-121)
Keywords: Ehime University -- The United Graduate School of Agricultural Sciences -- Dissertations; Food -- Analysis flavor